Using Spotify as a Learning Medium in Developing Students' Listening Comprehension - Frensiska, Nadila; Jamiluddin; Mashuri; Muhammad Arid (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study aimed to prove whether or not the use of Spotify can develop the listening comprehension of the tenth-grade students of SMA Negeri 2 Palu. The research design used in this study was a quasi-experimental design, and used a quantitative approach to analyze the data. The population of this study was the tenth-grade students of SMA Negeri 2 Palu. The researcher used purposive sampling and chose two groups: XD as the experimental group and XE as the control group, which each group consisted of 32 students. The instrument in collecting data was test (pre-test and post-test). The results of this study show that there is a significant difference in the increase in students' listening after being taught through the Spotify application. Data analysis shows that the tcounted (7,216) is higher than ttable (1,670) by applying a significance level of 0.05 with degrees of freedom (df) = 62. This means that the hypothesis is accepted. So, it can be said that Spotify can develop the students’ listening comprehension in learning English at SMA Negeri 2 Palu.